Identifying the factors influencing intention to purchase organic food and their relevance with time - Kaur , Harmandeep (Gyan Management Journal, 2023)
During the last few decades, demand for organic food has increased globally. Consequently, academic interest in understanding the different factors affecting organic food consumption has also increased. But, the scope of the previous studies is both broad and fragmented. There is an absence of a study that identifies the most important factors affecting the intention to purchase organic and changing relevance of these factors with time. The current study, on the basis of review of past studies, identifies the most important factors affecting the intention to purchase organic and identifies changing pattern of these factors with time. A total of 109 empirical studies were considered in this study. The primary outcomes of this research paper are: a) identification of the most important factors influencing intention to purchase organic food; b) changing relevance of these factors with time; c) implications for scholars and policymakers interested in understanding issues regarding organic food consumption.